Knowledge, awareness, and practice of biomedical waste segregation in a dental office - K Janani; Mahalakshmi Jayaraman (Wolters Kluwer Medknow Publications, 2022)
Biomedical waste (BMW) is any sort of litter generated in the course of human or animal research operations, such as diagnosis, treatment, or immunization, or during the development or trial of pharmaceutical products or in health camps. In dental sectors, BMW, if not adequately handled, can provide a number of health risks to dental practitioners, patients, and other dental healthcare service providers who operate in dental offices. The aim of the study is to examine the knowledge, awareness, and practice of BMW segregation among dental offices. A well-framed questionnaire containing 10 self-structured questions was formed and distributed among 100 students of dentistry through an online Google Forms link. The results were collected, tabulated, and statistically analyzed using the Software SPSS. Chi-square test was performed to assess the P value. Biological waste segregation was known to 98% of the participants, in which most of them had more than 10 years of expertise in dentistry. It is evident that dentists with a lot of experience over the years in the field of dentistry possess considerably increased awareness regarding the segregation of BMWs in their dental offices. Chi-square test done between the years of experience in dentistry and the knowledge on BMW segregation reveals that 0.031 < 0.05 is the P value, which is statistically significant. Most dentists having experience of above 10 years in the field of dentistry have excellent knowledge and practice of segregating BMWs in their dental offices.